(untitled) (Qualitative Research Journal for Social Studies, 2026)
This paper discusses the effects of rising nationalism on globalization, focusing on international trade, alliances, and cooperation in Europe, the United States, and Asia. It compares Brexit, the America First policy, and the China Belt and Road Initiative. It combines realism, liberalism, and constructivist theoretical outlooks through a qualitative comparative case study approach. The findings indicate that nationalism fails to prevent globalization but transforms it into selective, transactional and sovereignty-based interdependence. Trade policies have shifted toward strategic control, with a focus on protectionism, export controls, and supply chains aligned with political interests. The cohesion of alliances such as NATO, the EU, and ASEAN is also being eroded by domestic political pressures, which are eroding commitment and cooperation. Multilateral co-operation on climate change, migration, and global health has become more divided as states seek national sovereignty rather than collective action. The paper shows the necessity of progressive governance systems that balance the national agendas and international duties. This research offers evidence and theoretical understanding of the trend of nationalism that is changing the international order. It provides a guideline for policymakers and international organizations operating in a world becoming more nationalistic.